F(x) = 4x - 9
let f(x) = y, this implies that x = f⁻¹(y)
y = 4x - 9 Let us solve for x.
4x - 9 = y
4x = y + 9
x = (y + 9)/4
Recall that x = f⁻¹(y),
x = (y + 9)/4
f⁻¹(y) = (y + 9)/4
That means that for f⁻¹(x)
f⁻¹(x) = (x + 9)/4
Hope this explains it.
Answer: B each charm costs 15 dollars
Step-by-step explanation: because each money increment is 15$ so the answer is $15
~Brainliest would be appreciated
Answer:
1/2 X + X -15 + 1/2 X + 100 + X -25 = 540
1/2x + x + 1/2x + x -15 + 100 -25 = 540
3 x + 60 = 540
3x + 60 - 60 = 540 - 60
3/3x = 480/3
x = 160
Step-by-step explanation:
1/2 X + X -15 + 1/2 X + 100 + X -25 = 540
1/2x + x + 1/2x + x -15 + 100 -25 = 540
3 x + 60 = 540
3x + 60 - 60 = 540 - 60
3/3x = 480/3
x = 160
Answer:
D 40,000nm
Step-by-step explanation: 1nm/10^-9m * 10^-6/1um = 10^3 nm/um
Therefore in 40 microns there are:
40um * 10^3 nm/um = 40 * 10^3 nm = 40,000 nm